Оценка виброхарактеристик ротора с поперечной трещиной на жестких опорах по трехмерной модели - Шульженко, Н.Г.; Зайцев, Б.Ф.; Руденко, Е.К.; Асаенок, А.В. (Проблемы машиностроения, 2013)
На примере ротора цилиндра среднего давления паровой турбины Т-250/300-240 численно исследуется влияние поперечной трещины на его вибрационные характеристики при разных частотах вращения. Применяется трехмерная конечноэлементная модель ротора с учетом контактирования берегов трещины. Приводятся спектральные характеристики вибрационных перемещений ротора с трещиной. На прикладі ротора циліндра середнього тиску парової турбіни Т-250/300-240 чисельно досліджено вплив поперечної тріщини на його вібраційні характеристики при різних частотах обертання. Застосована тривимірна скінченноелементна модель ротора з урахуванням контактування берегів тріщини. Наводяться спектральні характеристики вібраційних переміщень ротора з тріщиною. The rotor of the intermediate-pressure cylinder of steam turbine Т-250/300-240 is used for investigating the influence of a transverse crack on its vibration condition with account of faces contact. The rotor is considered in the rotating coordinate system and modelled as a 3D body resting on rigid supports. The finite-element method is used, whereas the crack is modelled using a technique allowing to create on an arbitrary surface a layer of double nodes belonging to different faces of the crack. The matrices in the motion equation are built for a completely open crack, whereas the contact conditions on the crack faces are satisfied by introducing contact forces applied in the double nodes. The time solution of the problem is based on the Newmark scheme, and at each time step iterations determine the distribution of contact forces on the crack faces.